Modelagem numérica e gráfica da história das forças no território: uma proposta metodológica a partir da física estática - Wagmacker, Filipe dos Santos (2023)
From the backdrop of globalization, Castoriadis (1978) and Milton Santos (1996) suggested that new methods be created to encompass all the growing complexity of territories based on the uniqueness of disciplines in understanding issues of space x time. Studying the various Brazilian metropolises, Flávio Villaça (2001) realized that urbanization processes are the result of Forces applied in different directions and intensities and, as well as in structures, the result of these vectors would determine the movement of change or trend of urban growth. Therefore, we will embark on a research method classified as exploratory by Gil (2002), whose general objective is to carry out a numerical and graphic modeling of the incident actions, in order to allow analysis of the Forces of the territory from a Stress x Deformation graph based on in Physics and Resistance of Materials, thus creating a parameter for evaluating the Strengths of the territory. Therefore, the specific objectives are summarized in: applying the laws of Physics to the analysis of the Forces that affect the territory, defining a historical line in which it is possible to carry out a reading of the empirical object, a region that was called “Sertão de Santa Clara” , which resulted from a geographical cut that currently covers 7 municipalities and 13 locations, in a territory with an approximate area of 596 thousand km², between the states of Espírito Santo, Minhas Gerais and Bahia, whose tensions were detected by the study of the shape on a Regional scale . With these data, a Graph-Static analysis is achieved, considering the periods of elasticity, plasticity and rupture. Once again, philosophy, in this case that of Castoriadis' autonomy, gave meaning to mathematical methods for application in Physics. The relevance of the proposed method consists, in the future, of comparative analyzes of applications in several empirical objects, in the possibility of creating a database through which it is possible to predict the consequences of a force, helping in urban planning.